IN VITRO ANTIOXIDANT AND ANTI-INFLAMMATORY ACTIVITY OF THE FLOWER EXTRACTS OF OPUNTIA STRICTA - D, PRABHAKARAN; A, RAJESHKANNA; MM, SENTHAMILSELVI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to evaluate the antioxidant and anti-inflammatory activities of the solid powder obtained from the ethyl acetate fraction from the flower Opuntia stricta. Methods: The flower extract was evaluated for antioxidant activity by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay and reducing power assay was carried out by ferric-reducing capacity (FRC) assay method. The in vitro anti-inflammatory activity was evaluated using human peripheral blood mononuclear cells (PBMCs) stimulated by lipopolysaccharide (LPS) to evaluate nitric oxide (NO) production method. Results: The solid powder obtained from the ethyl acetate fraction from the flower O. stricta showed a good antioxidant activity in scavenging DPPH radical and FRC assay with compared standard sample. This solid powder also showed good anti-inflammatory activity in cell viability (LPS-induced PBMCs) assay and NO assay. Conclusion: These results suggest that the solid powder obtained from the ethyl acetate fraction from the flower O. stricta has significant antioxidant and anti-inflammatory activities.